Assessment of Beekeeping Knowledge among Farmers in Haryana - Subhash Chander; Bas Kaur; Joginder Singh Malik; Sahil Boora; Balkar Singh; Asha Rani Sheoran (Indian Journal of Extension Education, 2025)
The Indian economy, heavily reliant on agriculture, faces challenges due to increasing population pressure and declining landholding sizes, pushing farmers to diversify their income sources. Beekeeping, requiring minimal capital investment and leveraging natural resources like nectar and pollen, emerges as a viable alternative. This study, conducted in Kaithal, Kurukshetra, and Karnal districts of Haryana, aimed to assess farmers’ knowledge of beekeeping practices. A total of 150 respondents were surveyed using structured interviews and secondary data sources. The results revealed that most beekeepers had a moderate to high knowledge of various aspects of beekeeping, including honey production, bee flora, and biological aspects. Socio-economic factors such as age, education, social participation, and media exposure significantly influenced knowledge levels. Beekeeping not only enhances crop productivity through pollination but also offers employment opportunities, making it an essential strategy for rural development. The study emphasizes the potential of beekeeping in uplifting smallholder farmers and mitigating the limitations of traditional agriculture.